Synergistic effect in the co-extraction of Ginseng and Schisandra protein - Zhang, Han; Wang, Haidong; Zhou, Hongyan; Shi, Jialin; Wan, Zhiqiang; Li, Guangzhe; Yan, Mingming (Frontiers in Nutrition, 2024)
Introduction Ginseng and Schisandra are traditional Chinese plants that have been used in culinary practices and are renowned for their immune-boosting properties. In Chinese medicine, Ginseng and Schisandra are frequently used together as a clinical pair to mutually enhance their effect, producing a synergistic effect when consumed in combination. However, the underlying mechanism of their synergistic effect remains uncertain. Therefore, this study investigates the synergistic effect of Ginseng-Schisandra in terms of macromolecular proteins. Methods We used a dual-protein research methodology combined with co-extraction techniques to obtain the co-extracted protein of ginseng and Schisandra. We then compared the physicochemical and functional properties and antioxidant activities of co-extracted protein (COP), simple mixed protein (SMP), Ginseng protein (PGP), and Schisandra protein (SCP). Results Generally, PGP and SCP are considered as functional food with antioxidant activity. COP are composite proteins with a shared internal structure that are combined by Ginseng and Schisandra proteins, while SMP are simple mixtures of PGP and SCP. Free radical scavenging experiments indicated that COP exhibited the highest scavenging ability for hydroxyl radicals (98.89%), 1,1-diphenyl-2-picrylhydrazyl (DPPH) radicals (85.95%), and 2,2′-azinobis-(3-ethylbenzthiazoline-6-sulfonate) (ABTS+) radicals (42.69%). In vitro, COP significantly reduced the accumulation of reactive oxygen species (ROS) and malondialdehyde (MDA), while increasing intracellular levels of superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), catalase (CAT), and lactate dehydrogenase (LDH) levels in HepG2 cells. Discussion The comparative results of the macromolecular proteins reveal that COP contributes to the synergistic effect of Ginseng-Schisandra and indicate the advantages of co-extraction in protein production, suggesting the potential application of COP in the food industry.